Cross border marriage (CBM): a comparative study on the profiles and factors of CBM among Malays in Malaysia - Md Hashim, Noraini (2011)
Cross border marriage (CBM) is one of the solutions to legalise a marriage and is a common phenomenon involving both monogamous and polygamous eloped marriages. This polemic issue has occurred among the Malays (mainly among the followers of Shafie Mazhab) since a long time ago and still continues. This article examines the issue that CBM, which are rampant at present, will lead to uncertainty to the validity of marriages. This uncertainty will lead to problems in determining the status of the marriage and other claims in the marriages including matters involving children and inheritance. This article discusses factors that influence parties to contract CBM and violate the specified law and procedures. Qualitative and quantitative methods were employed in collecting information from the Shariah courts’ files pertaining to the profiles of parties to CBM in four selected states in Malaysia namely Kedah, Kelantan, Selangor and Johor. Data were collected using questionaires developed based on the Islamic Family Law Act and other legal literatures. Data were analysed by using descriptive statistical technique which revealed the general pattern of all variables understudied. The findings from this research are expected to fill in the gap in socio-legal literature in relation to Muslim marriages. It could provide valid justification to support the National Family Policy and to design any regulatory framework relating to the implementation and enforcement of Islamic family law in Malaysia. It is important to marry according to the law and procedures that have been laid down under the Islamic Family Law Act and Enactments so that appropriate protection provided under the law can be extended, especially to women and children whenever matrimonial problems arise.